2020
DOI: 10.3390/cancers12092672
|View full text |Cite
|
Sign up to set email alerts
|

The Pancreatic Microbiome is Associated with Carcinogenesis and Worse Prognosis in Males and Smokers

Abstract: An intra-pancreatic microbiota was recently discovered in several prominent studies. Since pancreatic adenocarcinoma (PAAD) is one of the most lethal cancers worldwide, and the intratumor microbiome was found to be a significant contributor to carcinogenesis in other cancers, this study aims to characterize the PAAD microbiome and elucidate how it may be associated with PAAD prognosis. We further explored the association between the intra-pancreatic microbiome and smoking and gender, which are both risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 27 publications
(32 reference statements)
0
71
0
Order By: Relevance
“…Chakladar et al profiled the intra-tumor pancreatic microbiome through large-scale sequencing data from The Cancer Genome Atlas (TCGA) (187 pancreatic cancer samples). The authors found that the increased prevalence and poorer prognosis of PDAC in males and smokers were linked to the presence of potentially cancer-promoting or immune-inhibiting microbes (most of them belonged to Proteobacteria phylum) [ 86 ]. Another study showed that intra-tumor Gammaproteobacteria in PDAC modulates tumor sensitivity to gemcitabine, one of the few active and standard of care chemotherapy drugs used in PDAC [ 38 ].…”
Section: Tumor-associated Microbiomementioning
confidence: 99%
“…Chakladar et al profiled the intra-tumor pancreatic microbiome through large-scale sequencing data from The Cancer Genome Atlas (TCGA) (187 pancreatic cancer samples). The authors found that the increased prevalence and poorer prognosis of PDAC in males and smokers were linked to the presence of potentially cancer-promoting or immune-inhibiting microbes (most of them belonged to Proteobacteria phylum) [ 86 ]. Another study showed that intra-tumor Gammaproteobacteria in PDAC modulates tumor sensitivity to gemcitabine, one of the few active and standard of care chemotherapy drugs used in PDAC [ 38 ].…”
Section: Tumor-associated Microbiomementioning
confidence: 99%
“…Of note, elevated levels of Proteobacteria were detected in fecal samples of patients with PDAC [41,45], making stool analysis an attractive, cheap, and non-invasive method to detect intrapancreatic microbial shifts. Some studies showed elevated levels of intratumoral Enterobacteriaceae, which also correlated with poor prognosis [35,37]. Moreover, another intestinal bacterium, Enterococcus faecalis, was identified within juice and tissue samples of PDAC-patients [40].…”
Section: The Bacterial Microbiome Of the Pancreatic Tissue And Pdacmentioning
confidence: 99%
“…The analysis of pancreatic samples and fluids from patients with PDAC compared to samples from patients with a healthy organ or with benign pathologies provided evidence that the pancreas is not a sterile organ [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] ( Table 1 ). In particular, the analysis of pancreatic cystic fluid revealed a specific bacterial ecosystem which may reflect the microbiota harbored within the pancreas [ 39 ].…”
Section: Microbiome Alterations and Pdacmentioning
confidence: 99%
See 2 more Smart Citations